Analisis Efektivitas Penerapan Tally Count Pada Aplikasi Java Support di Departemen Warehouse CV. Java (Jati Vision Raya) Cirebon Dengan Sistem HCI - Riyanto, Aris; Marlianita, Rini; Julfah, Aldani (POLITEKNIK LP3I, 2023)
This research is about Analysis of the Effectiveness of Tally Count Application in Java Support Applications in Warehouse Department CV. JAVA (Jati Vision Raya) Cirebon uses HCI system. This study aims to determine the results of analysis, obstacles and solutions regarding the application of tally count in java support applications using the HCI system. In addition, this study also aims to provide input for companies and add insight into literature at Politeknik LP3I Cirebon. The research method used is a qualitative method with a descriptive approach, where the author describes the results of observations and analyzes data obtained in the field using the HCI system analysis model. Data collection techniques used in this study are interviews, literature studies, and observations carried out directly in CV. JAVA. After analyzing and discussing the problem, the author concludes that in the application of tally count in the java support application there are still some obstacles in its application but the HCI system has been implemented well so that the application of tally count in the java support application in the warehouse department CV. JAVA (Jati Vision Raya) is already effective.